Factores Psicosociales Asociados A La Depresión En Adultos Mayores Del Municipio De Andalucía, Valle (2022)
The present work was carried out in the San Vicente de Paul nursing home in the period from February to June 2022. The sample collected was 10 subjects, of which 8 were selected for the analysis of the study. The subjects were chosen under the inclusion criteria: older adults of both sexes aged 65 years and over, who present cognitive impairment, have cognitive functions within the normal range, and symptoms related to geriatric depression